Relationship between Clinical Examination, Ultrasonography, and Histopathological Findings in Breast Tumors - Muh Asri Jaya; Nasrudin Andi Mappaware; Berry Erida Hasbi; Reeny Purnamasari; Febie Irsandy (Universitas Muhammadiyah Surabaya, 2026)
Breast cancer is a global health issue and one of the leading causes of death among women in Indonesia, accounting for approximately 65% of cases. Various factors, such as lifestyle, genetics, and delayed diagnosis, contribute to the high mortality rate. This study aims to analyze the application of triple diagnosis, which includes clinical examination, ultrasound, and histopathology in the diagnosis of breast tumors at Ibnu Sina Hospital in Makassar. This study used an observational analytic design with a cross-sectional approach. A total sampling method was applied to all breast tumor patients who underwent clinical examination, ultrasonography, and histopathological examination during 2023–2024. Data were obtained from medical records and analyzed descriptively using frequencies and percentages. The association between clinical examination, ultrasonography, and histopathological findings was assessed using the Chi-square test. The results showed that most patients were young women and that benign tumors were more common than malignant tumors. Clinical examination and ultrasonography findings were predominantly benign. Histopathological examination showed that fibroadenoma mammae was the most common benign tumor, while invasive breast carcinoma of no special type was the most common malignant tumor. The Chi-square test showed a significant association between clinical examination, ultrasonography, and histopathological findings. These findings indicate diagnostic concordance among the three examination methods and support the role of integrated diagnostic assessment in assisting clinical decision-making for breast tumor management.